Air quality monitoring in the amang industry - Suki , A.; Zainal Abidin, Azman (1990)
Particulate monitoring was carried out at three amang- factories. The monitoring was carried put both inside (at the most "dusty" areas) and outside the factories. The levels inside were found to be extremely high ranging from 1572 to 21,664 ug/m3 . These were well above the WHO recommended level of 500-900 ug/m3, considered acceptable for a work environment. The levels outside, were also high ranging from 63 to 995 ug/m3. The recommended ambient level is 150 ug/m3. The results also implied that the suspended particulates were generated from the factory activities itself, and that the size of these particulates was within the size range that is hazardous to health. While the size of the amang and its processed products was large and as such unlikely to be suspended for long in the air, the fact that the suspended particulate concentration was high suggested that during processing the amang, impact and abrasion amongst the particles could result in their surfaces being chipped thus producing finer particulates.